John H. Johnson: A Historical Study on the Re-Education of African Americans in Adult Education Through the Selfethnic Liberatory Nature of Magazines - Margena A. Christian (Adult Education Research Conference, 2014)
This qualitative study explored the selfethnic liberatory educative nature and goals of John H. Johnson’s work between 1942 and 2005 as a pioneering publisher and adult educator. The research documented the influence his magazines, EBONY and Jet, had as approaches of informal learning to combat the impact of sociocultural, psychological and intellectual racism on African Americans.